Pasolini, Os Lusíadas e o 25 de Abril - Marnoto, Rita (2023)
(2023). Pasolini, Os Lusíadas e o 25 de Abril. In Rita Marnoto & Ana Beatriz Andrade. Pier Paolo Pasolini 100 Anos (89-108). Coimbra: Secção de Estudos Italianos da Faculdade de Letras da Universidade de Coimbra. ISBN 978 989 8511 10 2